Halotropism: Phytohormonal Aspects and Potential Applications - Szepesi, Ágnes (Frontiers in Plant Science, 2020)
Halotropism is a sodium specific tropic movement of roots in order to obtain the optimal salt concentration for proper growth and development. Numerous results suggest that halotropic events are under the control and regulation of complex plant hormone pathway. This minireview collects some recent evidences about sodium sensing during halotropism and the hormonal regulation of halotropic responses in glycophytes. The precise hormonal mechanisms by which halophytes plant roots perceive salt stress and translate this perception into adaptive, directional growth forward increased salt concentrations are not well understood. This minireview aims to gather recently deciphered information about halotropism focusing potential hormonal aspects both in glycophytes and halophytes. Advances in our understanding of halotropic responses in different plant species could help these plants to be used for sustainable agriculture and other future applications.